2020
DOI: 10.1007/s00520-020-05853-8
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers’ support needs during allo-HSCT—a longitudinal study

Abstract: Purpose The study aimed to explore family caregivers’ support needs prior to allo-HSCT, how these change over time and whether they are associated with demographic factors and caregiver outcome. Methods This longitudinal repeated measure study included 87 family caregivers of allo-HSCT recipients: 63% were partners, 74% women, 65% lived with the recipient, and their mean age was 54 years. They completed the 14-item Carer Support Needs Assessment Tool (CSNAT) and caregiver outcome measures (caregiver burden, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Family caregivers in the present study reported most need of additional support with Knowing what to expect in the future and Having time for yourself in the day . This is in line with the results from a study using the CSNAT among Swedish family caregivers of patients going through allogenic stemcell transplantion [ 35 ] and family caregivers in United Kingdom [ 30 ], Australia [ 36 ] and China [ 37 ]. Lowest QoL was reported in the QOLLTI-F domains related to the Patient condition, and Family caregivers’ own state.…”
Section: Discussionsupporting
confidence: 86%
“…Family caregivers in the present study reported most need of additional support with Knowing what to expect in the future and Having time for yourself in the day . This is in line with the results from a study using the CSNAT among Swedish family caregivers of patients going through allogenic stemcell transplantion [ 35 ] and family caregivers in United Kingdom [ 30 ], Australia [ 36 ] and China [ 37 ]. Lowest QoL was reported in the QOLLTI-F domains related to the Patient condition, and Family caregivers’ own state.…”
Section: Discussionsupporting
confidence: 86%
“…Family caregivers in allo-HSCT experience a high sense of uncertainty prior to transplantation due to, among other things, the lack of information about the patient's disease and the side effects of treatment (Bergkvist et al, 2020). The unique life situation of family caregivers in allo-HSCT comprising of high responsibility, a great sense of uncertainty about the future and long-term worries, is also explained by the patient's high risk of relapse and that her/his health status can change rapidly, which causes concern about what will happen next (Kuba et al, 2017; Bergkvist et al, 2018; Kisch et al, 2020). If family caregivers are prepared for the tasks and demands of the caregiving role prior to allo-HSCT, their situation during the distressing time of the allo-HSCT trajectory might be easier.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that the presence of floor effects may lower the tool’s responsiveness to change and may fail to capture the full range of support needs [ 37 , 38 ]. Limited studies have reported that the vast majority of CSNAT items did not change over time [ 13 , 39 ]. Longitudinal tobit regression model can be considered to account for the presented floor effects in future studies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%